Are Public-Private Partnerships a Healthy Option? A Systematic Review. - ROEHRICH, Jens K. (Institutional Knowledge at Singapore Management University, 2014)
Governments around the world, but especially in Europe, have increasingly used private sector involvement in developing, financing and providing public health infrastructure and service delivery through public–private partnerships (PPPs). Reasons for this uptake are manifold ranging from rising expenditures for refurbishing, maintaining and operating public assets, and increasing constraints on government budgets stifle, seeking innovation through private sector acumen and aiming for better risk management. Although PPPs have attracted practitioner and academic interest over the last two decades, there has been no attempt to integrate the general and health management literature to provide a holistic view of PPPs in healthcare delivery. This study analyzes over 1400 publications from a wide range of disciplines over a 20-year time period. We find that despite the scale and significance of the phenomenon, there is relatively limited conceptualization and in-depth empirical investigation. Based on bibliographic and content analyses, we synthesize formerly dispersed research perspectives into a comprehensive multi-dimensional framework of public-private partnerships. In so doing, we provide new directions for further research and practice.